Double Jeopardy Reimagined: Gendered Racism in the Retelling of the Ramayana in Amish Tripathi’s Ramachandra Series - Mr. B. Manojkumar,; Dr. R. Vithya Prabha,; Dr. S. Sudha, (The Bioscan, 2025)
Gendered Racism is considered to be the idea of double jeopardy because the individual is discriminated with two excluded identities. It is clearly projected in the myths like Ramayana and Mahabharata. Mythology serves as a guide for the formation of society. Through its social and economic hierarchy, every nation formulates its ideologies that facilitate the division of classes. Class differences not only create stagnation but also feed prejudice and gender inequity in society. Amish Tripathi is popular for his mythological series Ramachandra series highlights his characters by speaking for themselves, refuting traditional ethics made them strong, defy convention, remain truthful to the spirit of inquiry, master the secret art of perseverance, and carve out a place for themselves in a world that always appears to be working against them. This article exposes and analysis the sufferings of household women, abuse of lassie and depicts the social construct of disability and also proves that double jeopardy leads the humanity into the path of destruction.